Answer:
m = 2
General Formulas and Concepts:
Pre-Algebra
Order of Operations: BPEMDAS
- Brackets
- Parenthesis
- Exponents
- Multiplication
- Division
- Addition
- Subtraction
Equality Properties
Explanation:
Step 1: Define Equation
m - 4m = -6
Step 2: Solve for m
- Combine like terms: -3m = -6
- Divide -3 on both sides: m = 2
Step 3: Check
Plug in m into the original equation to verify it's a solution.
- Substitute in m: 2 - 4(2) = -6
- Multiply: 2 - 8 = -6
- Subtract: -6 = -6
Here we see that -6 does indeed equal -6.
∴ m = 2 is the solution to the equation.